La légende du windigo dans la création autochtone contemporaine au Québec - Isabelle St-Amand (Itinéraires, 2015)
Working with the notions of ethics and sovereignty developed in the field of Indigenous literary studies in North America, this article examines the uses of the legend of the windigo in contemporary Indigenous creation, more specifically in a francophone context. In contrast with the Western construction of the windigo psychosis, this article focuses on the conceptualization of a recurring violence in the short fiction film Windigo by Anishnabe director Kris Happyjack-McKenzie.